Family characteristics associate with risk taking behaviour among urban and rural adolescents in two districts in Selangor. A comparative study - Abdul Hamid, Siti Hazariah; Mohammed Nawi, Azmawati (Elsevier, 2013)
Risk taking behaviour has rated as one of the public health issue that need special attention. The objectives are to compare the prevalence and its associate factors in urban and rural. The results showed risky behaviour had no association with location of study and the prevalence were 81.7% (urban) and 84.7% (rural). Most of the parental factors unrelated to risky behaviour. Multiple logistic regressions had shown being a male, inadequate number of bedrooms, large number of household, family conflict and no family cohesion were the negative predictor in both areas. Hence, it is necessity for parents to protect their children as they must face utmost challenges during transitional period.